Pengaruh Kepemilikan Institusional, Tingkat Utang, dan Karakteristik Perusahaan terhadap Manajemen Pajak (Studi Empiris Pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bei Tahun 2017-2021) - Aditya Alfredo Situmorang; Nani Sriyani (CV Edujavare Publishing, 2024)
This research aims to determine the influence of institutional ownership, level of debt and company characteristics on tax management (empirical study of property and real estate sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period) both partially and simultaneously. This type of research is quantitative. The samples in this research were obtained using purposive sampling techniques, resulting in 9 samples obtained for the 2017-2021 research period. The data used in this research was obtained from financial reports. The tests used in this research are descriptive statistical tests, selection of panel data regression estimation models, classical assumption tests, and hypothesis tests. Data were analyzed using the Eviews 9 tool. The results of this research are that based on a simultaneous test of Institutional Ownership, the level of Debt and Company Characteristics influence Tax Management. Partially, Debt Levels have no effect on Tax Management. Institutional Ownership and Company Characteristics influence Tax Management.